CD8+CD28− T cells: key cytotoxic players impacting disease pathogenesis in chronic HBV infection. (13th September 2019) - Nandi, Madhuparna; Pal, Sourina; Ghosh, Sumantra; Chakraborty, Bidhan Chandra; Dey, Debangana; Baidya, Ayana; Shil, Achintya; Chattopadhyaya, Saran; Banerjee, Soma; Santra, Amal; Chowdhury, Abhijit; Datta, Simanti
Abstract : During chronic hepatitis B (CHB), CD8 + T cells down-regulate CD28, the primary co-stimulation molecule for T-cell activation. Diverse functional attributes of CD8 + CD28 − T cells are suggested in various disease contexts. The present study aimed to characterize CD8 + CD28 − T cells in different phases of chronic Hepatitis B virus (HBV) infection (CHI)- Immune-tolerance (IT), Hepatitis B e-antigen-positive CHB (EP-CHB), Inactive carriers (IC) and Hepatitis B e-antigen-negative CHB (EN-CHB), to appraise their contribution in HBV-related disease pathophysiology. Flow cytometry analysis of T cells in peripheral blood of study subjects revealed enhanced CD8 + CD28 − T-cell accumulation in EP-/EN-CHB, compared with IT/IC and they expanded equivalently in HBV-specific and non-specific CD8 + T-cell compartments. Profound increase in CD8 + CD28 − T cells expressing perforin/granzyme-B/CD57/IFN-γ/TNF-α and markers of terminal differentiation were observed exclusively in EP-/EN-CHB. Further, activation with anti-NKG2D resulted in heightened IFN-γ/TNF-α production selectively from CD8 + CD28 − T cells, suggesting NKG2D-mediated alternative co-stimulation. CD8 + CD28 − T cells sorted from CHB patients induced enhanced apoptosis of peripheral blood mononuclear cells (PBMC), including CD4 + T cells. However, NKG2D-ligand (major histocompatibility complex class I chain-related molecule A/B (MICA/B)) was preferentially expressed by HBV-specific CD4 + T cells of CHB patients, making these cells a potential target to NKG2D-dependent CD8 + CD28 − T-cell killing. Both CD28 + and CD28 − T cells in CHB expressed CXCR3 at similar levels and thus capable of homing to the liver. A positive correlation was seen between CD8 + CD28 − T-cell frequency and serum-alanine transaminase (ALT) levels and CHB-derived CD8 + CD28 − T cells caused pronounced cell death in HBV-transfected Huh7 cells. Immunofluorescence staining identified greater intrahepatic incidence of CD8 + CD28 − T cells but decline in CD4 + T cells in CHB than IC. Collectively, CD8 + CD28 − T cells demonstrated differential distribution and phenotypic/functional skewing in different CHI phases and contribute to disease progression by Perforin-Granzyme- or IFN-γ-TNF-α-mediated cytotoxicity while restraining antiviral immunity through NKG2D-dependent HBV-specific CD4 + T-cell depletion.